2012
DOI: 10.1371/journal.pone.0039555
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Assessment of the Availability and Use of Obstetric Care in Nigerian Healthcare Facilities

Abstract: BackgroundAs part of efforts to reduce maternal deaths in Nigeria, pregnant women are being encouraged to give birth in healthcare facilities. However, little is known about whether or not available healthcare facilities can cope with an increasing demand for obstetric care. We thus carried out this survey as a rapid and tactical assessment of facility quality. We visited 121 healthcare facilities, and used the opportunity to interview over 700 women seeking care at these facilities.FindingsMost of the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 8 publications
2
38
0
Order By: Relevance
“…These facilities were also clustered around the urban and peri urban areas, adjacent to the roads while a large proportion of people in the rural and remote areas remain virtually without services. This finding corroborates those of a study done in Nepal to assess the geographical distribution of facilities 19 and another study carried out in Zambia which reported that geographical access to EmOC services in rural areas was very low with less than 25% of the population living within 15km of any EmOC facility 20 .…”
supporting
confidence: 89%
“…These facilities were also clustered around the urban and peri urban areas, adjacent to the roads while a large proportion of people in the rural and remote areas remain virtually without services. This finding corroborates those of a study done in Nepal to assess the geographical distribution of facilities 19 and another study carried out in Zambia which reported that geographical access to EmOC services in rural areas was very low with less than 25% of the population living within 15km of any EmOC facility 20 .…”
supporting
confidence: 89%
“…Of these, 3 publications met the inclusion criteria and were included in our analysis (Ethiopia, The Gambia, and Nigeria) 19 - 21 . The studies for Ethiopia and Nigeria focused specifically on electricity access for facilities providing emergency obstetric and newborn care services.…”
Section: Resultsmentioning
confidence: 99%
“…The reluctance of health care staff to use assisted vaginal delivery for fear of maternal and neonatal complications is unjustified. It reveals a lack of provider training and experience, both of which are determinants of the outcome of vacuum- or forceps-assisted delivery [16, 19]. In Lubumbashi, this lack of training is one of the main obstacles to the introduction of vacuum extraction by ventouse as the tool of choice for instrument-assisted delivery.…”
Section: Discussionmentioning
confidence: 99%